The Detection of Cheating on E-Exams in Higher Education—The Performance of Several Old and Some New Indicators - Ranger, Jochen; Schmidt, Nico; Wolgast, Anett (Frontiers in Psychology, 2020)
In this paper, we compare the performance of 18 indicators of cheating on e-exams in higher education. Basis of the study was a field experiment. The experimental setting was a computer assisted mock exam in an introductory course on psychology conducted at a university. The experimental manipulation consisted in inducing two forms of cheating (preknowledge, test collusion) in a subgroup of the examinees. As indicators of cheating, we consider well established person-fit indices (e.g., the U3 statistic), but also several new ones based on process data (e.g., response times). The indicators were evaluated with respect to their capability to separate the subgroup of the cheaters from the remaining examinees. We additionally employed a classification tree for detecting the induced cheating behavior. With this proceeding, we aimed at investigating the detectability of cheating in the day-to-day educational setting where conditions are suboptimal (e.g., tests with low psychometric quality are used). The indicators based on the number of response revisions and the response times were capable to indicate the examinees who cheated. The classification tree achieved an accuracy of 0.95 (sensitivity: 0.42 / specificity: 0.99). In the study, the number of revisions was the most important predictor of cheating. We additionally explored the performance of the indicators to predict the specific form of cheating. The specific form was identified with an accuracy of 0.93.